2002
DOI: 10.1051/animres:2002014
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of once-daily milking and feeding level in the first three weeks of lactation on milk production and enzyme activities, and nutritional status, in Holstein cows

Abstract: -Twenty-four multiparous cows were divided into 4 groups immediately after calving according to a 2 × 2 factorial design: 2 milking frequencies (1 daily [morning only] milking for the first three weeks of lactation, then 2 daily milkings vs. 2 daily milkings throughout) under two diet energy concentrations (normal or low). The trial lasted 30 weeks, on average, and ended in the pasture on 28 May 2000. During the winter period, the cows were housed together in a free-stall barn, and were given complete rations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 26 publications
10
37
4
2
Order By: Relevance
“…This fall is consistent with earlier observations of a reduction of lipolysis with increased interval between milkings (Chilliard and Lamberet, 1984;Klei et al, 1997) and with a lowered LPL activity in OAD (Ré mond et al, 2002 and (and here), although we observed no individual correlation between these parameters. The relative fall in FFA, which was much more marked than that of the LPL activity (267% v. 227%), suggests that other mechanisms are brought into play.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This fall is consistent with earlier observations of a reduction of lipolysis with increased interval between milkings (Chilliard and Lamberet, 1984;Klei et al, 1997) and with a lowered LPL activity in OAD (Ré mond et al, 2002 and (and here), although we observed no individual correlation between these parameters. The relative fall in FFA, which was much more marked than that of the LPL activity (267% v. 227%), suggests that other mechanisms are brought into play.…”
Section: Discussionsupporting
confidence: 93%
“…The OAD cows demonstrated their discomfort (vocalisations) for a shorter time than in an earlier trial conducted in early lactation where they were separated from the TAD cows every evening at the time of milking (Ré mond et al, 2002), suggesting that it was the separation of the group rather than the skipped milking that caused these effects. This confirms the conclusion of a recent study (Tucker et al, 2007) that behavioural indices do not suggest that cow welfare is impaired by OAD milking.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the variation in milk fat content observed over the different weeks of the ODM period can explain the contradictory effects reported in various studies. Some studies reported an increase in milk fat content (Stelwagen et al, 1994;Lacy-Hulbert et al, 1999;O'Brien et al, 2002) but others reported no variation (Ré mond et al, 2002;Marnet and Komara, 2008) or a decrease (Ben Chedly et al, 2011) in milk fat content during ODM. Our finding suggests that the inhibition of milk fat synthesis by ODM may gradually disappear beginning in the second week of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Criterion 6: As grass is the main production in mountain areas, not competing with human feeding, farmers may also choose breeds with a lower milk yield than Holstein cows that can be fed with grass forages only. In the case of highyielding cows, farmers may also shorten the periods when the animals have high needs by milking the cows only once a day from calving, to reduce the lactation peak (Rémond et al, 2002) or by extending the interval between calving (Auldist et al, 2007). In addition, grouping the calving in spring allows the production of most milk at pasture, which requires less concentrate for a similar milk yield, as the feeding value of grazed swards is always higher than that of the corresponding preserved forage.…”
Section: Preserving Biological Diversity In Agroecosystems By Adaptinmentioning
confidence: 99%